2015
DOI: 10.1001/jamainternmed.2015.3006
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy for Insomnia Comorbid With Psychiatric and Medical Conditions

Abstract: IMPORTANCE Cognitive behavioral therapy for insomnia (CBT-I) is the most prominent nonpharmacologic treatment for insomnia disorders. Although meta-analyses have examined primary insomnia, less is known about the comparative efficacy of CBT-I on comorbid insomnia.OBJECTIVE To examine the efficacy of CBT-I for insomnia comorbid with psychiatric and/or medical conditions for ( 1) remission from insomnia; (2) self-reported sleep efficiency, sleep onset latency, wake after sleep onset, total sleep time, and subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
252
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(290 citation statements)
references
References 67 publications
16
252
0
2
Order By: Relevance
“…However, a meta-analysis including studies of differing treatment duration found similarly large effects, such as observed in this trial, in those with comorbid insomnias. 63 Similarly, it is possible that the therapy was not potent enough because it was delivered by novices (i.e., graduate students). Although fidelity to the protocol was measured formally, there was no formal competence evaluation beyond the observation of the students and weekly supervision of these sleep-therapy naive novice therapists.…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis including studies of differing treatment duration found similarly large effects, such as observed in this trial, in those with comorbid insomnias. 63 Similarly, it is possible that the therapy was not potent enough because it was delivered by novices (i.e., graduate students). Although fidelity to the protocol was measured formally, there was no formal competence evaluation beyond the observation of the students and weekly supervision of these sleep-therapy naive novice therapists.…”
Section: Discussionmentioning
confidence: 99%
“…Within the CBT-I trial literature, it is not uncommon for TST to show minimal or no improvement posttreatment. 6,11 Given the brevity of the intervention period (4 to 6 w) and the focus on sleep restriction, it is not entirely surprising that changes in TST were not observed. Indeed, actigraphic sleep assessment showed shorter TST from the pretreatment to posttreatment period, which is consistent with the goals of sleep restriction (i.e., to minimize time awake in bed).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 There is a large evidence base supporting the efficacy of cognitive behavioral therapy for insomnia (CBT-I) among adults with a diverse range of comorbid physical and psychiatric conditions. 6 In contrast, CBT-I is still in early stages of development within child and adolescent populations.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, many patients with insomnia have an inadequate response to pharmacologic therapy, as was present in the article by Rezaeitalab et al, and cognitive behavioral therapy for insomnia (CBTi). In a metaanalysis of CBTi in comorbid medical and psychiatric disorders, only 36% of patients were in remission after treatment [15]. Supporting the role that Boccult^sleep disordered breathing is present in many patients with refractory insomnia is an article by Krakow et al that reported 90% of nocturnal awakenings in patients with chronic insomnia only (no suspicion of OSA) were due to respiratory events [16].…”
mentioning
confidence: 99%